Analisis Onomatope dalam Bahasa Jepang dan Bahasa Jawa - Fitri Alfarisy; Muhammad Rayhan Baihaqy; Adi Prasetyo Utomo; Nur Afifurrohman (Publikasi Indonesia, 2022)
Sounds made by objects or human voices can form a word. Words formed by imitation of sound are onomatopoeia. In this study the author discusses 'Onomatopoeic Analysis in Japanese and Javanese. This study intends to analyze the similarities and differences on onomatopoeia in Japanese and Javanese. This research will go through three stages of research, namely, data collection, data analysis, and exposure of the results of data analysis. The data collection method in this research is literature study. Onomatopoeia in Japanese includes giseigo, giongo, gitaigo, giyougo, and gijougo. Meanwhile, the word onomatopoeia in Javanese can be said to be small when compared to onomatopoeic research in other languages. It can be concluded that onomatopoeia in Japanese and Javanese have similarities and differences. The similarities are in the classification, usage, and form of the word, while the difference is in the naming.